Association of Serum Myeloid Cells of Soluble Triggering Receptor-1 Level with Myocardial Dysfunction in Patients with Severe Sepsis - Fei Tao; Liangshan Peng; Juan Li; Yiming Shao; Liehua Deng; Huaguo Yao (Mediators of Inflammation)
Objective. To investigate the association of serum sTREM-1 with myocardial dysfunction in patients with severe sepsis. Methods. A total of 85 patients with severe sepsis were divided into severe sepsis group (n=40) and septic shock group (n=45). Serum levels of sTREM-1, NT-proBNP, APACHE II score, SOFA score, cardiac index, cardiac function index, global ejection fraction, and left ventricular contractility index were measured on days 1, 3, and 7 after admission to ICU. Results. Serum sTREM-1 levels of patients with septic shock were significantly higher than those with severe sepsis on days 1, 3, and 7. Serum sTREM-1 was positively correlated with APACHE II scores, SOFA scores, and NT-proBNP. However, The sTREM-1 level was markedly negatively correlated with CI, CFI, GEF, and dP/dt max, respectively. Multiple logistic regression analysis showed that sTREM-1 was independent risk factor to NT-proBNP increasing. The optimal cut-off point of sTREM-1 for detecting patients with myocardial dysfunction was 468.05 ng/mL with sensitivity (80.6%) and specificity (75.7%). There is no difference in TREM-1-mRNA expression between the two groups. Conclusions. Serum sTREM-1 is significantly associated with myocardial dysfunction and may be a valuable tool for determining the presence of myocardial dysfunction in patients with severe sepsis.